Characterization of the chloroplast genome of Lagerstroemia villosa Wall. ex Kurz. (Lagerstroemia, Lythraceae) - Wang, Jie (Mitochondrial DNA B Resour, 2021)
Lagerstroemia villosa is a kind of ornamental tree with surprising potential for applying in the landscape. We characterized the complete chloroplast genome of this scarce species and analyzed its phylogeny within Lythraceae. The result showed that the genome possessed a typical quadripartite structure, in more detail, a lager single-copy region (LSC, 88,702bp), a small single-copy region (SSC, 18,255bp), and a pair of inverted repeat regions (IRa and IRb, 26,906 bp). 78 protein-coding genes, four ribosomal RNA (rRNA) genes, and 30 transfer RNA (tRNA) genes were detected. Phylogenetic analysis based on maximum likelihood (ML) supported the closest relationship between L. villosa and Lagerstroemia limii plus Lagerstroemia subcostata.